2015
DOI: 10.1002/pssb.201552407
|View full text |Cite
|
Sign up to set email alerts
|

Impact of acceptor concentration on the resistivity of Ni/Au p‐contacts on semipolar (20–21) GaN:Mg

Abstract: The p‐type doping of GaN with Mg, in particular doping of p++ cap layers and its influence on the resistivity of Ni/Au contacts on semipolar (20–21) GaN, has been investigated. For this purpose, we have compared GaN:Mg grown on several semipolar and polar orientations with respect to the acceptor concentration NA measured by electrochemical capacitance voltage techniques. For the same Mg precursor flow and Mg/III ratio, we observe very similar acceptor densities NA of up to 1 × 1019 cm−3 for (0001), (20–21), (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…5). This may bedue to a p ++ layer with lower amount of Mg compared to (0001) [as also indicated by recent results on (2021) 21 ]. Another reason could be the much higher tendency of (1122) to incorporate oxygen, i.e.…”
Section: Doping and Contactsmentioning
confidence: 57%
See 1 more Smart Citation
“…5). This may bedue to a p ++ layer with lower amount of Mg compared to (0001) [as also indicated by recent results on (2021) 21 ]. Another reason could be the much higher tendency of (1122) to incorporate oxygen, i.e.…”
Section: Doping and Contactsmentioning
confidence: 57%
“…It was previously reported that the (1122) surface needs a 2-3 times higher Cp 2 Mg flow rate than the (0001) surface to obtain a similar Mg incorporation. 10,20,21 Hence, first we targeted the Cp 2 Mg flow rate. When a certain Cp 2 Mg flow rate was exceeded, we observed many dark spots in the optical microscope [ Fig.…”
Section: Doping and Contactsmentioning
confidence: 99%
“…Ni/Au electrodes were evaporated on the surface of the samples after annealing activation. [12,13] To realize good ohmic contact, the electrodes were annealed at 600 °C in air atmosphere for 60 s. I-V measurements were carried out to test the contact between the electrode and p-GaN. As shown in Figure 5, the p-GaN layer grown on the c-plane FS-GaN substrate can achieve a good ohmic contact with the annealed Ni/Au electrode.…”
Section: Resultsmentioning
confidence: 99%
“…The samples were grown on commercial 3.5 μm standard Si doped GaN ( n = 1.7 ×10 18 cm −3 ) on (0001) direction sapphire substrates in a T‐shape horizontal flow low‐pressure metal organic vapor phase epitaxy (MOVPE) reactor . First, the epitaxial growth of the p‐GaN layer was optimized which is a crucial for achieving good quality ohmic contact to p‐GaN . Samples with 150 nm thick nominally doped p‐GaN followed by 50 nm thick highly doped p‐GaN were grown on the templates.…”
Section: Methodsmentioning
confidence: 99%